Empowerment through advertisements: the social responsible role of depicting images of special needs for normalcy - Mokhtar, Aida (Zes Rokman Resources, 2019)
Media messages are capable of fashioning our perception of reality through the empowerment of distinctive images of people with special needs. Without the existence of special needs representation in advertising, the inclusion of people with special needs in mainstream society could be absent. The act of normalizing distinctions through dignified portrayals of special needs people who are diverse could be an additional function of advertising in addition to bringing people together at the marketplace when selling products. An organization involved in normalizing people with special needs as part of society is doing a noble act that should be encouraged similar to upholding the visibility of a brand. Several objectives could be met through advertising from inculcating positive attitudes to special needs people, encouraging values in people, normalizing special needs people by mainstream society to promoting goodwill to the organization. Without such visible depictions, people with special needs could encounter possible exclusion from society initiated by a negative attitude to them. Values such as compassion and empathy could be communicated through these depictions and inculcated within the audience. These efforts could be part of the organization’s initiative in being socially responsible.